Hermeneutics solution to the environmental problem of the biosphere facing globalization of anthropocentrism (REVISTA NODO, 2014)
It aims to show hermeneutics proposal to dissolve the ideological causes of the environmental problem. To achieve this, first conceptual causes of environmental problems are located in the anthropocentric categorization of globalization and industrial development. Second, some of these causes are analyzed from the premises of an environmental ethic to dissolve the debate between anthropocentrism (exploitation and commercialization of land limited only profit) and radical biocentrism (extreme and unalterable nature conservation). This is used as the theory of interpretation, technically named hermeneutic, to conceptualize and properly interpret the concept of biosphere. This allows the fusion between industrial globalization meanings and values of the habitat and its inhabitants.
Keywords: Anthropocentrism; globalization; environment; biosphere; solution of horizons